# Solve System of Linear Equations with Elimination and Substitution

## Grade 8 Math Worksheets

### Schedule a Free session to clear worksheet doubts

*No credit card required, no obligation to purchase. *

*Just schedule a FREE Sessions to meet a tutor and get help on any topic you want!*

### Let’s see this with the help of an example –

3*x* – 4*y* = 11 …Equation (1)

-3*x* + 2*y* = -7 …Equation (2)

When we add the two equations, *x*-terms will be eliminated. This happens because the coefficients of the *x*-terms, 3 and -3, are opposites of each other.

So, adding we get:

Dividing both sides by -2, we get, *y* = -2

Now put *y* = -2 back in equation (1) or equation (2) to get the value of *x*. Let us put *y* = -2 in equation (1):

3*x* – 4(-2) = 11 3*x* + 8 = 11

3*x* = 11 – 8 3*x* = 3

*x*** = 1**

**Check the solution: **Put *x* = 1 and *y* = -2 in the given equations to check the answer.

Left Hand Side (L.H.S) of the equation 3*x* – 4*y* = 11:

3(1) – 4(-2) = 3 + 8 = 11, which is the same as right Hand Side (R.H.S) of the equation.

Since L.H.S = R.H.S, so the values are correct.

Similarly, L.H.S of the equation -3*x* + 2*y* = -7:

-3(1) + 2(-2) = -3 – 4 = -7, which is the same as R.H.S of the equation.

Since L.H.S = R.H.S, so the values are correct.

## Personalized Online Tutoring

eTutorWorld offers affordable one-on-one live tutoring over the web for Grades 2-12, Test Prep help for Standardized tests like SCAT, CogAT, SSAT, SAT, ACT, ISEE and AP. You may schedule online tutoring lessons at your personal scheduled times, all with a Money-Back Guarantee. The first one-on-one online tutoring lesson is always FREE, no purchase obligation, no credit card required.

For answers/solutions to any question or to learn concepts, take a **FREE Demo Session**.

*No credit card required, no obligation to purchase. *

*Just schedule a FREE Sessions to meet a tutor and get help on any topic you want!*

*Example*: Solve the given system of equations by elimination method –

5*x* – 4*y* = 9 …Equation (1)

*x* – 2*y *= -3 …Equation (2)

Here we can either multiply equation (2) by 5 so that the coefficient of *x* in equation (2) is also 5 and then we can subtract both the equations to get the value of *y*, or we can multiply equation (2) by ‘-2’ and then add the two equations to get the value of *x*.

Here we multiply equation (2) by -2, and then add the equations –

5*x* – 4*y* = 9 …Equation (1) ——————— 5*x* – 4*y* = 9 …Equation (1)

*x* – 2*y *= -3 …Equation (2) ——————— -2*x* + 4*y *= 6 …Equation (2)

Adding the equations we get, 5x – 2x = 9 + 6

3*x* = 15

Dividing by 3 we get, *x* = 5

Put this value of *x* = 5 in any of the two equations to get the value of *y*, putting *x* = 5 in equation (2) we get:

5 – 2*y* = -3

2*y* = 5 + 3

2*y* = 8 implies *y* = 4

**Check the solution:**

L.H.S of the equation 5*x* – 4*y* = 9:

5(5) – 4(4) = 25 – 16 = 9, which is equal to the R.H.S of the equation.

L.H.S of the equation *x* – 2*y *= -3:

5 – 2(4) = 5 – 8 = -3, which is equal to the R.H.S of the equation.

** Example:** Solve the following equations for

*x*and

*y*:

2*x* + *y* = 3 …Equation (1)

-5*x* + *y* = -4 …Equation (2)

** Step 1**: From equation (1),

*y*= 3 – 2

*x*

** Step 2 and 3**: Put

*y*= 3 – 2

*x*in equation (2)

*, –*5

*x*+ (3 – 2

*x*) = -4

-5x – 2x = -4 – 3

-7x = -7 ⇒ *x* = 1

** Step 4**: Put

*x*= 1 in equation (1),

*y*= 3 – 2

*x*

*y = *3 – 2(1)

*y *= 3 – 2

** y = 1**

** Step 5**:

**Check the solution:**Put

*x*= 1 and

*y*= 1 in any of the given equations to check the answer.

Left Hand Side (L.H.S) of the equation 2*x* + *y* = 3:

2(1) + 1 = 2 + 1 = 3, which is equal to the R.H.S of the equation.

Since L.H.S = R.H.S so, the values are correct.

L.H.S of -5*x* + *y* = -4:

-5(1) + 1 = -5 + 1 = -4, which is equal to the R.H.S of the equation.

Since L.H.S = R.H.S so, the values are correct.

## Check Point

- Solve by elimination method:

*x* + *y* = 1

*x* – *y* = 3

- Solve by substitution method:

* x* + 2*y* = 2

-4*x* + 3*y* = 25

- Solve by elimination method:

2*x* + 5*y* = -4

3*x* – *y* = 11

- Solve by substitution method:

5*x* + 2*y* = 0

*x* – 3*y* = 0

- Solve by elimination method:

*x* = 4*y *– 2

*x* = 6*y* + 8

##### Answer key

- (2, -1)
- (-4, 3)
- (3, -2)
- (0, 0)
- (-22, -5)

### Schedule a Free session to clear worksheet doubts

*No credit card required, no obligation to purchase. *

*Just schedule a FREE Sessions to meet a tutor and get help on any topic you want!*

## Pricing for Personalized Online Tutoring

Tutoring Package | Validity | Grade (1-12), College |
---|---|---|

5 sessions | 21 Days | $114 |

1 session | 21 Days | $24 |

10 sessions | 2 months | $219 |

15 sessions | 3 months | $319 |

20 sessions | 3 months | $409 |

50 sessions | 6 months | $949 |

100 sessions | 10 months | $1849 |

## IN THE NEWS

Home

Summer Courses 2021

Tutoring

Test Prep

Worksheets

Pricing

About Us

Blog

Free Trial

Login

Terms of service

Privacy Policy

Money Back Guarantee

Technical requirements

FAQs

Job Opportunities

Sitemap

**Connect with us**

+1-269-763-4602

+1-269-763-5024

**Online test prep and practice**

SCAT

CogAT

SSAT

ISEE

PSAT

SAT

ACT

AP Exam

**Science Tutoring**

Physics Tutoring

Chemistry Tutoring

Biology Tutoring

**Math Tutoring**

Pre-Algebra Tutoring

Algebra Tutoring

Pre Calculus Tutoring

Calculus Tutoring

Geometry Tutoring

Trigonometry Tutoring

Statistics Tutoring

©2021 eTutorWorld Terms of use Privacy Policy Site by Little Red Bird

©2021 eTutorWorld

Terms of use

Privacy Policy

Site by Little Red Bird